Performance evaluation of contractor development programmes in South Africa. Issue 1 (2nd January 2017) - Dapaah, Ambrose D.; Thwala, Wellington D.; Musonda, Innocent
Abstract : The performance of the construction industry in South Africa is supported by its industry players, such as the construction contractors, and cannot be underestimated. The designed Contractor Development Programmes (CDPs) in South Africa are aimed at creating an enabling environment for the survival and sustainability of Small, Medium and Micro Enterprise (SMME) contractors. Despite the prime aim of the CDPs in facilitating sustainable growths among SMMEs, the CDPs, however, have not been adequately evaluated by their beneficiaries, according to existing literature. Therefore, the need for a study to investigate the impact of the CDPs on beneficiaries is prudent and formed the rational for this study. The aim of this study was to carry out performance evaluation from the perspective of the CDP beneficiaries. Questionnaire survey and structured interviews were adopted using construction SMMEs as the study population who were selected via the purposive sampling technique. This method was appropriate because it gave respondents the opportunity to express their views on the impact of the CDPs. The study found that beneficiaries were comparatively satisfied with the CDPs but requested that they should be given a face-lift to upgrade them and make them more sustainable. The study also established that there are gaps in the CDPs that the implementing agencies should cover to ensure the successful implementation of the CDPs. Further, the study concluded that continuous mentorship programmes for contractors is an apparent solution where performance of CDPs is inadequate, but that this vital component of training is lacking in most South African CDPs.